2020
DOI: 10.1101/2020.08.06.239731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular motion and tridimensional nanoscale localization of kindlin control integrin activation in focal adhesions

Abstract: Focal adhesions (FAs) initiate chemical and mechanical signals involved in cell polarity, migration, proliferation and differentiation. Super-resolution microscopy revealed that FAs are organized at the nanoscale into functional layers from the lower plasma membrane to the upper actin cytoskeleton. Yet, how FAs proteins are guided into specific nano-layers to promote interaction with given targets is unknown. Using single protein tracking, super-resolution microscopy and functional assays, we linked the molecu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…7J; Fig. S8D) with a diffusion constant D diff = 0.087 ± 0.001 µm 2 .s -1 (mean ± SEM) that is comparable to that of free diffusing transmembrane proteins (integrins: (Rossier et al, 2012)) or of a lipid-anchored protein bound to the plasma membrane by its PH domain (kindlin:(Orre et al, 2021). Confined SEPT9_i3-mEos3.2 was also diffusing very slowly (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…7J; Fig. S8D) with a diffusion constant D diff = 0.087 ± 0.001 µm 2 .s -1 (mean ± SEM) that is comparable to that of free diffusing transmembrane proteins (integrins: (Rossier et al, 2012)) or of a lipid-anchored protein bound to the plasma membrane by its PH domain (kindlin:(Orre et al, 2021). Confined SEPT9_i3-mEos3.2 was also diffusing very slowly (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…A case in point is the molecular dynamics linked to focal adhesion (FA) zones. For instance, some proteins, such as Rac1 and kindlin, are targeted to the membrane where they can undergo free diffusion before being recruited to and confined at these zones 37,38 . By contrast, proteins such as talin and PIX are directly recruited from the cytoplasm to these zones and become confined 37,38 .…”
Section: Mainmentioning
confidence: 99%
“…For instance, some proteins, such as Rac1 and kindlin, are targeted to the membrane where they can undergo free diffusion before being recruited to and confined at these zones 37,38 . By contrast, proteins such as talin and PIX are directly recruited from the cytoplasm to these zones and become confined 37,38 . Why proteins choose different recruitment pathways appears to be dictated by their functions and is still a matter of intense investigation.…”
Section: Mainmentioning
confidence: 99%
“…Li et al, 2017; Liu et al, 2011). This domain triggers the localization of kindlin at the membrane and promotes its diffusion, allowing kindlin to reach and activate integrins (Orré et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the same study showed that in cells kindlin increases integrin affinity for multivalent but not monovalent extracellular ligands, suggesting a role for kindlin in talin-activated integrin clustering. Interestingly, tracking of single proteins in cells revealed that talin associates with integrins in FAs from a cytoplasmic pool (Rossier et al, 2012), whereas kindlin membrane diffusion allows kindlin to reach FAs and activate integrins (Orré et al, 2021). Furthermore, the association of kindlin with integrins is more labile than that of talin, indicating that these two regulators may also act sequentially or independently of each other.…”
Section: Introductionmentioning
confidence: 99%